Cyrtodactylus wangkulangkulae (Squamata: Gekkonidae), a new Bent-toed Gecko from Satun Province, southern Thailand - Sumontha, Montri; Pauwels, Olivier S. G.; Suwannakarn, Nikorn; Nutatheera, Thammarat; Sodob, Watchira (Zootaxa, 2014)
We describe a new Cyrtodactylus from Manang District, Satun Province, southern Thailand, based on an adult female having a snout-vent length of 73.9 mm, a long tail (1.34 times snout-vent length), a complex blotched and banded dorsal pattern with four irregularly shaped dark bands between limbs insertions, bluish-grey iris, discontinuous series of enlarged poreless femoral and precloacal scales, 10 regularly arranged dorsal tubercle rows, 38 ventral scale rows between ventrolateral skin folds, transversely enlarged subcaudal plates, and no precloacal groove.